Color‐Changing Soft Actuators: Biomimetic Color Changing Anisotropic Soft Actuators with Integrated Metal Nanowire Percolation Network Transparent Heaters for Soft Robotics (Adv. Funct. Mater. 32/2018). (6th August 2018) - Kim, Hyeonseok; Lee, Habeom; Ha, Inho; Jung, Jinwook; Won, Phillip; Cho, Hyunmin; Yeo, Junyeob; Hong, Sukjoon; Han, Seungyong; Kwon, Jinhyeong; Cho, Kyu‐Jin; Ko, Seung Hwan
Abstract : In article number1801847, Jinhyeong Kwon, Seung Hwan Ko, and co‐workers report a novel color changing anisotropic thin film actuator. Various color‐shifting biomimetic soft robots are demonstrated, including a color‐changing blooming flower, a fluttering butterfly, and a color‐changing twining tendril. The electro‐thermally operating soft actuators with an installed metal nanowire network heater allows easy programming of actuation direction and instantaneous visualization of temperature changes through color‐shift.